Reassembling the Archive: Datafication and the Digital Afterlife of Early Public Officials in 19th-century Greece - Chrysanthopoulos, Christos; Charamopoulos, Leonidas; Festas, Michael; Koniali, Christina; Liagka, Margarita; Sarafis, Vangelis; Dimitropoulos, Dimitris; Seirinidou, Vaso (Journal of Integrated Information Management, 2025)
Purpose — This paper explores the epistemological implications of datafication in historical research through the case study of the BioState project, which digitally reconstructs the careers of early public officials in 19th-century Greece. The project demonstrates how archival traces are reassembled as structured data, creating an administrative archive that never existed in institutional form. Design/methodology/approach — The study is based on the implementation of a semantic relational database using the Heurist platform, which models historical records as interconnected entities. Methodologically, the project integrates ontology-driven data modeling, archival documentation, and interpretive strategies to convert fragmentary sources into a coherent digital prosopographical system. Findings — BioState highlights that datafication is not a neutral act of digitization but a performative reconstitution of historical meaning. The project reveals how archival traces, originally non-standardized and dispersed, are transformed into a queryable knowledge system. Originality/value — This work contributes to digital historiography by advancing a theoretical and practical model for reconstituting absent or fragmented archives. It proposes that the digital archive should be seen not as a repository of the past but as a performative apparatus that enacts new forms of historical visibility. The concept of the "digital afterlife" is introduced to describe how bureaucratic traces acquire renewed significance within computational environments.